2020
DOI: 10.1111/age.12959
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype‐based genome‐wide association studies reveal new loci for haematological and clinical–biochemical parameters in Large White pigs

Abstract: SummaryWe report haplotype‐based GWASs for 33 blood parameters measured in 843 Italian Large White pigs. In the single‐trait analysis, a total of 30 QTL for number of basophils, six erythrocyte traits (haemoglobin, haematocrit, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration, mean corpuscular volume and red blood cell count) and two clinical–biochemical traits (alkaline phosphatase and Ca2+ contents) were identified. In the multiple‐trait analysis, a total of five QTL affected three di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
3
8
1
Order By: Relevance
“…It is also clear that alleles (haplotypes) with low MAF could potentially identify falsepositive QTL regions. However, higher estimated genomic heritability of the haplotype analysis in this breed might indicate that most of the haplotype-detected QTL regions are actually true QTL regions, as we already reported in another study using a similar approach (Bovo et al 2020a). Moreover, the low MAF at several QTL regions in this breed (captured by the haplotypes; Fig.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It is also clear that alleles (haplotypes) with low MAF could potentially identify falsepositive QTL regions. However, higher estimated genomic heritability of the haplotype analysis in this breed might indicate that most of the haplotype-detected QTL regions are actually true QTL regions, as we already reported in another study using a similar approach (Bovo et al 2020a). Moreover, the low MAF at several QTL regions in this breed (captured by the haplotypes; Fig.…”
Section: Discussionsupporting
confidence: 61%
“…GWAS may benefit from utilising haplotypes instead of SNPs to establish marker‐phenotype associations (Lorenz et al 2010 ; Barendse 2011 ). We recently demonstrated that by using haplotypes in GWAS it is possible to detect genomic regions affecting targeted phenotypes that could not be detected with a single‐marker approach and vice versa (Bovo et al 2019 , 2020a ). The additional information that could be extracted might be dependent on the particular mutational and recombination history between QTL alleles and the genotyped markers, which in turn, might be affected by possible ascertainment biases derived by the construction of the SNP genotyping panels used in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…First QTL were detected using microsatellites (e.g., [ 26 , 27 ]) or concentrated on particular genes (e.g., [ 28 30 ]). Other studies to detect immune relevant QTL vary widely in treatment, methods of phenotype determination and breed (e.g., [ 10 , 31 37 ]). In addition, different ages and developmental stages are covered, limiting the comparability of the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Although the same algorithm to obtain the haplotype blocks was used in our study and in Veroneze et al (2013), they used a threshold of at least 3 SNPs (we used 2). On the other hand, the number of haplotype blocks identified in our population was smaller than the number of haplotype blocks identified in a Large White population of 21,296 (Bovo et al, 2020). LD is expected to be lower in crossbred populations and, consequently, the number of haplotype blocks is also expected to be smaller than in purebred lines (Fu et al, 2015).…”
Section: Identification Of Haplotypescontrasting
confidence: 66%